Quantum algorithms for topological and geometric analysis of data - Seth Lloyd (Nature Portfolio, 2016)
Persistent homology allows identification of topological features in data sets, allowing the efficient extraction of useful information. Here, the authors propose a quantum machine learning algorithm that provides an exponential speed up over known algorithms for topological data analysis.